A study on the evaluation of university students on the information quality and credibility of online political information - Sayana, Jethro G. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
People on the Internet have encountered online political information as it is produced and promulgated on a daily basis. Misinformation can be spread in this manner hence there is a need for online users to utilize standards and criteria to filter each and very information. This study tries to investigate the factors young Filipino particularly University of the Philippines college students, may use as a basis for their evaluation of online political information. Factors derived from the respondents were sorted through the criteria of information quality and credibility. Actions that they may do during and after the evaluation were also accounted for.